Agni Karma To Manage Sandhigata VataW.S.R. To Cervical Spondylosis : A Review - Suden, Akshay (International Research Journal of Ayurveda & Yoga, 2020)
The human body experiences continuous degenerative changes with age. The degeneration is very commonly observed, especially in the inter-vertebral discs in between the cervical vertebrae at higher ages. This leads to the start of problematic symptoms in the neck region. Neck pain is the worst amongst them. Neck stiffening & inability to perform movements are the other complications and the associated disease is the Sandhigata vata (cervical spondylosis), for which there is as yet no permanent cure available in the modern system of medicine. Symptoms in the extremity may also develop due to irritation of nerve supplying it. This disease can, however be effectively managed following the Ayurvedic system. Sandhigatavata(Cervical spondylosis) is the result of aggravated Vata Dosha with anubandha of kapha avarana. However, dhatu kshaya is also the excitatory factor responsible for vitiation of vata dosha. The review of the recently published articles and the classical Ayurvedic literature amply demonstrate the efficacy of the classical Agni- Karma technology in mitigating the Sandhigata vata (Cervical spondylosis) disease. Besides this, Agni-Karma is a safe, non invasive and drug free para-surgical procedure. It is also, a cost effective procedure, requiring no hospitalization, etc. Since, the incidence of this disease has been observed mostly in the higher age bracket, the technology can, therefore be made more patient friendly by incorporating appropriate rasayana drugs, abhyanga, anti-inflammatory medicines, etc.